2022
DOI: 10.1002/adfm.202209241
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Anisotropic Polariton Lasing Using Molecular Conformation and Orientation in Organic Microcavities

Abstract: Organic exciton-photon polariton lasers are promising candidates for the efficient generation of coherent light at room temperature. While their thresholds are now comparable with those of conventional organic photon lasers, tuning of molecular conformation and orientation as a means to control fundamental properties of their emission and thus further enhance performance remains largely unexplored. Here, a two-fold reduction in the threshold of a microcavity polariton laser based on an active layer of poly(9,9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The high penetration depth of the field into the reflectors reduces the available volume for molecules, reducing the average molecular density and thus the coupling strength. Another aspect is that the transition dipole moment and the vacuum electric field are vectors, which underlines the importance of their relative orientation. , …”
Section: Strong Light–matter Interaction Essentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high penetration depth of the field into the reflectors reduces the available volume for molecules, reducing the average molecular density and thus the coupling strength. Another aspect is that the transition dipole moment and the vacuum electric field are vectors, which underlines the importance of their relative orientation. , …”
Section: Strong Light–matter Interaction Essentialsmentioning
confidence: 99%
“…Another aspect is that the transition dipole moment and the vacuum electric field are vectors, which underlines the importance of their relative orientation. 30 , 70 72 …”
Section: Strong Light–matter Interaction Essentialsmentioning
confidence: 99%
“…Under these conditions of strong light–matter coupling, hybridization of photons and excitons can lead to the formation of two new eigenstates called the upper and lower polariton . Strong coupling thus allows manipulation of the light and matter components of a system in new ways and therefore enables the design of devices with a number of interesting properties and with possible applications, e.g., in transistors, communication systems, and polariton lasers. In addition, very recently, we have demonstrated that strong coupling and, in particular, the unique angular dispersion relation of polaritons can be used to generate angle independent emission with high color purity, which might have profound implications for the design of future displays . In order to be able to directly manipulate these systems using strong light–matter coupling, efficient polariton OLEDs must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of organic polaritons by Lidzey et al [1], many fascinating phenomena have been demonstrated in the strong coupling regime, such as high-temperature polariton condensation and superfluid transition [6][7][8][9], stimulated scattering [10], and optically pumped polariton lasing [11][12][13]. More recently, organic microcavities in the ultrastrong coupling regime (Rabi-splitting exceeds 20% of the exciton transition energy [14]) have been further achieved, bringing the prospect of non-classical physics and innovative device applications [15][16][17][18][19]. It is shown that strongly coupled materials are not specifically limited to the narrow-band absorbing molecules such as J-aggregate dyes [20,21].…”
Section: Introductionmentioning
confidence: 99%